Bildung through social media - Michael Paulsen; Jesper Tække (Netcom)
In this article we argue that ‘the media situation’ of the digital age brings new possibilities of Bildung (i.e. emancipation and edification). Through comparing the situation ‘before’ and ‘after’ the internet, we detect a change in the communicative infrastructure of teaching. Before the internet we see teaching taking place in closed classrooms almost without interactional contact with the surrounding world. In this setting Bildung is mainly made possible through ‘internal interaction’ and representation of knowledge about the world. After computers, wireless networks and smartphones has entered the scene we see teaching taking place in communicatively open classrooms with possibilities of interactional contact with “outsiders.” In this setting Bildung is not only made possible through knowledge about the world, but also through internet-mediated interaction with others. Through an uncovering of these new possibilities we conclude that social media like Twitter can be used to support ‘interactional Bildung.’ Empirically, we base our argument on an action research project called ‘Socio Media Education.’ We carried out this project in a Danish upper secondary school class. An important element was that the class and its teachers had to use Twitter for written interaction in all subjects. Theoretically we base our argument on educational theory (Kant, Klafki, Biesta), medium theory (Eisenstein and others) and sociology (Luhmann and Goffman).